Analisis Perbandingan Kadar Metabolit Primer Daun Pisang Kepok Kuning (Musa Paradisiaca L.) Hasil Kultur Jaringan Dan Tanaman Konvensional - Frianda, Dwi Dicka; Dalimunthe, Nur Asyiah; Sahfitra, Angga Ade (Jurnal Ilmiah Pertanian ( JIPERTA), 2026)
This study aims to compare the primary metabolite content of yellow Kepok banana (Musa paradisiaca L.) leaves obtained through tissue culture and conventional cultivation methods. Yellow Kepok banana is one of Indonesia’s superior varieties with high economic value and great potential as a raw material for the food industry and as a source of value-added biomass. In the context of agricultural biotechnology, tissue culture techniques not only enable rapid and uniform plant propagation but may also influence the biochemical composition of plants through more controlled growth conditions. This study employed a descriptive experimental design with two treatments and three replications. Primary metabolites analyzed included carbohydrates, proteins, fats, crude fiber, ash, and moisture content, using the proximate (AOAC) method. The results showed that leaves derived from tissue culture had higher levels of carbohydrates (44.15% DM), proteins (19.77% DM), and fats (7.82% DM) compared to conventionally grown plants (39.93% DM; 16.13% DM; 6.20% DM). Conversely, conventionally grown leaves contained higher crude fiber, ash, and moisture. Controlled tissue culture conditions enhanced physiological efficiency and energy metabolite accumulation, whereas natural environments favored structural component formation. These findings highlight the potential of tissue culture as an effective method for producing banana leaf biomass with improved nutritional and metabolite profiles.